Anaemia presenting as the sole symptom in a young woman: A case of malignant peripheral nerve sheath tumour of the small intestine - Sohail, Mushtaq; Sze Kiat, Sim; Nik Azim, Nik Abdullah (Malaysian Medical Association, 2025)
Malignant peripheral nerve sheath tumours (MPNSTs) with gastrointestinal involvement are uncommon. We report the case of a 22-year-old woman presenting with symptomatic anaemia requiring recurrent blood transfusions. Initial haematological evaluations revealed microcytic hypochromic anaemia. Both upper and lower endoscopies were normal, except for a positive rapid urease test result. However, computed tomography identified a tumour originating from the ileum and adherent to the urinary bladder, along with a mixed-density lesion in the right ovary. Following multidisciplinary team discussion, en-bloc resection of the ileal tumour and enucleation of the ovarian lesion, were performed. Histopathological analysis confirmed the ileal mass as an MPNST and the ovarian lesion as a benign cystic teratoma. This case highlights the rarity of ileal MPNSTs presenting with anaemia and emphasises the importance of complete surgical excision and vigilant follow-up owing to the potential for recurrence and metastasis.